Contributions of Central Command and Muscle Feedback to Sympathetic Nerve Activity in Contracting Human Skeletal Muscle - Boulton, Daniel; Taylor, Chloe E.; Macefield, Vaughan G.; Green, Simon (Frontiers in Physiology, 2016)
During voluntary contractions, muscle sympathetic nerve activity (MSNA) to contracting muscles increases in proportion to force but the underlying mechanisms are not clear. To shed light on these mechanisms, particularly the influences of central command and muscle afferent feedback, the present study tested the hypothesis that MSNA is greater during voluntary compared with electrically-evoked contractions. Seven male subjects performed a series of 1-minute isometric dorsiflexion contractions (left leg) separated by 2-minute rest periods, alternating between voluntary and electrically-evoked contractions at similar forces (5-10 % of maximum). MSNA was recorded continuously (microneurography) from the left peroneal nerve and quantified from cardiac-synchronised, negative-going spikes in the neurogram. Compared with pre-contraction values, MSNA increased by 51 ± 34 % (P < 0.01) during voluntary contractions but did not change significantly during electrically-evoked contractions (-8 ± 12 %, P > 0.05). MSNA analysed at 15-s intervals revealed that this effect of voluntary contraction appeared 15-30 s after contraction onset (P < 0.01), remained elevated until the end of contraction, and disappeared within 15 s after contraction. These findings suggest that central command, and not feedback from contracting muscle, is the primary mechanism responsible for the increase in MSNA to contracting muscle. The time-course of MSNA suggests that there is a longer delay in the onset of this effect compared with its cessation after contraction.